PENGARUH MUTASI JABATAN TERHADAP KINERJA PEGAWAI PADA PT PEGADAIAN (PERSERO) KANTOR WILAYAH PEKANBARU - Aqsa, Muhammad Ali; Olivia, Febi (Eko dan Bisnis: Riau Economic and Business Review, 2017)
The study was posted on PT. Personnel (Persero) Pekanbaru Regional Office, as for the purpose of this study is to find out how much influence the position mutation on employee performance at PT. Personnel (Persero) Regional Office Pekanbaru. As for the population in this study are all employees who have received mutations during work that amounted to 33 employees. While the sample in this study amounted to 33 people with saturated sample approach. Data analysis used to measure this research using descriptive and quantitative method by performing simple linear regression. The results obtained in this study through SPSS 19 data processing showed that the value of independent variables (mutation of positions) on t test obtained t count value of 3,500 is greater than the value of t table of 2.039. based on the above results can be concluded that Ho is rejected, it means that the position mutations significantly affect the performance of employees at PT Pegadaian (Persero) Regional Office Pekanbaru. The big influence of the variable of position mutation on employee performance is 28.3% while the rest of 71.7% is influenced by other factors which are not careful in this research